Kesaksian Notaris Mengenai Akta Perjanjian Kredit Berkaitan Dengan Rahasia Jabatan Notaris Dalam Peradilan Pidana - Ayu Made Semilir Susila, I Gusti (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 1 No 1 (2016), 2016)
Notary in performing his position must be able to keep the trust given by the parties in the form of notary position secret as set out in Law Number 30 Year 2004 and Law Number 2 Year 2014. Notary gives his service in many fields of civil law, including in banking field. Banking institution in performing its business activity is also obliged to keep its customer secret in the form of bank secret, as set out in Law Number 10 year 1998. Notary’s position in the case of giving his service to make bank credit agreement deed does not set clearly in Banking Law. Later this also causes unclear thing in limiting notary’s responsibility in giving evidence regarding credit agreement deed in the case that the bank has been excluded for the interest of criminal judicature. The type of this research is normative law research which starts from the existence of haziness regarding notary position in Banking Law and its amendment, and norm haziness regarding notary responsibility in giving evidence about credit agreement deed in criminal judicature. This research uses law, conceptual, and historical approach. The law material used in this research is primary law material, secondary law material, and tertiary law material. The law material collection technique used is literature study. The result shows that notary in giving his service to make bank credit agreement deed has position as affiliated party. It brings consequence that notary responsible to keep the things set as bank secret. In his position as witness in criminal judicature, notary responsible and shall to give evidence related to the things set in the beginning or head of the deed and the things related to the making process of a bank credit agreement deed to be able to be said as authentic deed that has perfect verification authority, but notary does not responsible in giving evidence in accordance with the things including bank secret category.
Keywords: Notary Evidence, Credit Agreement Deed, Notary Position Secret, Criminal Judicature